Effective renewable energy activities in Bangladesh - Islam, A.K.M. Sadrul; Islam, Mazharul; Rahman, Tazmilur (ScienceDirect, 2006)
Bangladesh is endowed with plentiful supply of renewable sources of energy. Out of the various renewable sources, solar and biomass and to a limited extend, wind and hydro-power are effectively used. This paper, discusses the effective applications of these resources. Bangladesh receives an average daily solar radiation of 4-6.5 kWh/m2. Solar photovoltaic (PV) are gaining acceptance for providing electricity to households and small business enterprises in grid remote rural areas. Under the 'Rural Electrification and Renewable Energy Development (RERED) Programme' a total of 64,000 SHSs will be installed by 2007. So far, a total of 37,000 SHSs with a capacity of about 2.5 MWp have been installed in the country. The next effective source of renewable energy is biomass. Under this category improved stoves, bio-gas plant and bio-mass briquitting are note worthy. The Institute of Fuel Research and Development (IFRD) has developed a number of improved stoves. These stoves save 50-70% fuel as compared to the traditional ones. So far, more than 100,000 stoves have been installed in the users kitchens. The potential of biogas technology is immense. According to an official estimates there is a cattle population of 24 million and poultry population of 75 million. This can produce about 3 billion m3 biogas. The Local Government Engineering Department (LGED) and IFRD are working to install the biogas plants in the rural areas. So far, a total of 19,596 biogas plants have been installed. Khulna University of Engineering and Technology (KUET) has successfully under took a research and development work on biomass briquitting technology with a grant from SIDA. By now, this technology has transferred to private entrepreneurs. Currently, about 60 small private enterprises are producing briquettes from rice husk and saw dust. Because the country is flat, hydropower is not abundant. At present, 230 MW is harnessed from the Kaptai dam. Besides, in the southeastern hilly regions a few micro-hydro sites have been identified. Very recently, one 10 kW micro-hydro plant has been installed by LGED at Bamerchara in Chittagong. Wind energy potential is not encouraging except in the coastal areas of Bangladesh. A few wind turbines have been installed as demonstration units. A project is going on for wind mapping of the country by LGED